The correlation between vaginal pathogens and high-risk human papilloma virus infection: a meta-analysis of case-control studies - Yang, Jun; Long, Xin; Li, Sijing; Zhou, Min; Hu, Li-Na (Frontiers in Oncology, 2024)
BackgroundSystematic study on the relationship between vaginal microbiota and high-risk human papillomavirus infection (HR-HPV) is limited. Hence, the aim of this study is to investigate the correlation between vaginal microbiota and HR-HPV infection through a meta-analysis of case-control studies.MethodsChinese Journal Full-text database, Wanfang database, PubMed database, VIP Chinese Science and Technology Journal database, Web of Science, ScienceDirect, ProQuest, JSTOR, Wiley, and IEEE Xplore were synthetically searched for studies about the correlation between vaginal microbiota and HR-HPV infection. Revman 5.3 software was used to assess the relationship between vaginal microbiota and HPV infection through meta-analysis. Finally, forest map was used to calculate the results and funnel plot was applied to test the publication bias.ResultsFourteen independent studies were admitted in this study, containing a total of 21, 446 women in gynecological outpatients. Compared with HR-HPV negative group, the prevalence of bacterial vaginosis (BV) [odds ratio (OR)=2.45, 95% confidence intervals (CI): 1.83-3.27, P<0.00001], Ureaplasma urealyticum (UU) (OR=1.38, 95% CI: 1.23-1.54, P<0.00001), and Chlamydia trachomatis (CT) (OR=3.53, 95% CI: 2.82-4.41, P<0.00001) increased in HR-HPV positive group through meta-analysis, while, there was no significant difference in the prevalence of trichomonal vaginitis (TV) (OR=1.69, 95% CI: 0.97-2.96, P=0.06) and vulvovaginal candidiasis (VVC) (OR=0.91, 95% CI: 0.54-1.51, P=0.71.ConclusionsVaginal pathogens are closely related to HR-HPV infection. When BV, UU, and CT are abnormal, the risk of HR-HPV infection is increased.